2017
DOI: 10.1136/bmjgh-2017-000371
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of two sequential artemisinin-based combination therapy regimens to treat uncomplicated falciparum malaria in African children: a protocol to investigate safety, efficacy and adherence

Abstract: BackgroundManagement of uncomplicated Plasmodium falciparum malaria relies on artemisinin-based combination therapies (ACTs). These highly effective regimens have contributed to reductions in malaria morbidity and mortality. However, artemisinin resistance in Asia and changing parasite susceptibility to ACT in Africa have now been well documented. Strategies that retain current ACT as efficacious treatments are urgently needed.MethodsWe present an open-label, randomised three-arm clinical trial protocol in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Studies with isogenic lines expressing one or two copies of pfmdr1 showed no difference in MFQ IC 50 values (Dhingra et al, 2017), and some isolates have been found to carry multicopy pfmdr1 and plasmepsin II (Bopp et al, 2018), suggesting that resistance to both drugs in a single parasite is possible. Similarly, changing the dosing regimen to ''sequential double ACT'' may be sufficient to overpower transient dormancy-like ART resistance and is also being tested in a clinical trial (Schallig et al, 2017). In contrast, ''split dosing,'' i.e., splitting a once-daily dose into a twice-daily dose to increase daily ART exposure, did not increase the efficacy of ART, likely because splenic parasite clearance was exceeded (White et al, 2017).…”
Section: Implications For Treatment and Future Research Outlookmentioning
confidence: 99%
“…Studies with isogenic lines expressing one or two copies of pfmdr1 showed no difference in MFQ IC 50 values (Dhingra et al, 2017), and some isolates have been found to carry multicopy pfmdr1 and plasmepsin II (Bopp et al, 2018), suggesting that resistance to both drugs in a single parasite is possible. Similarly, changing the dosing regimen to ''sequential double ACT'' may be sufficient to overpower transient dormancy-like ART resistance and is also being tested in a clinical trial (Schallig et al, 2017). In contrast, ''split dosing,'' i.e., splitting a once-daily dose into a twice-daily dose to increase daily ART exposure, did not increase the efficacy of ART, likely because splenic parasite clearance was exceeded (White et al, 2017).…”
Section: Implications For Treatment and Future Research Outlookmentioning
confidence: 99%
“…This platform could also be utilized for the evaluation of sequential ACT therapy, another proposed modification to existing ACT therapy to improve clinical efficacy and reduce the emergence of drug resistant parasites. In such protocols two different approved ACTs would be administered sequentially over 6 days (two three-day 22 treatments), ideally with partner drugs with validated mechanisms of action that exert opposing pressure on genetic determinants that modulate drug susceptibility (53). During the second half of treatment, there would be remaining exposure of the initial ACT partner drug, thereby establishing a three-day timeframe of triple-drug exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In the next section, arguments based on the parasite cell cycle will be used to support this unorthodox suggestion, and lend further support to the strategy of extended artemisinin regimens to radically cure P. falciparum infections [25].…”
Section: The Perceived Threat To Artemisinin-based Malaria Therapeuticsmentioning
confidence: 99%
“…Certainly, there is no doubt that K13-independent artemisinin susceptibility phenotypes have arisen [10,36], and may continue to arise in the future, under universal selection pressure from ACT deployment worldwide. This threat makes it imperative that strategies to preserve the efficacy of our current regimens are vigorously pursued in the short term, as we await the next generation of antimalarial drugs [25].…”
Section: K13-independent Artemisinin Susceptibility Phenotypes In Plamentioning
confidence: 99%
See 1 more Smart Citation